ASSESSMENT OF STRESS AMONG NURSING STUDENTS DURING THEIR TRAINING TENURE AT JINNAH COLLEGE OF NURSING (The Research of Medical Science Review, 2024)
Nursing is an art and science. It's a hard-hitting, emotionally taxing, and highly disciplined career. The demands of both the classroom and the clinical setting place a heavy burden on nursing students during their training. Academic stress, students confront a variety of academic issues. Clinical stresses like receiving negative feedback from teachers in a clinical environment. This study aims  to assess the degree of stress and coping strategies among nursing students at Jinnah College of Nursing. In this observational, cross-sectional study, 105 participants were randomly selected of which 36.2% were male and 63.8% were female. The mean age of the majority was 22 ± years and they were mostly single 92 (87.6%). 50% of nursing students reported feeling stressed about their clinical experiences and academic achievement, 34% did not, and 16% were neutral. The main stressors were fewer vacations/ breaks (56; 53.3%), lack of guidance from teachers (19; 18.1%). 73.3% of nursing students reduce their stress by applying coping strategies. The findings revealed that majority of nursing students were under severe academic and clinical stress. The study suggests that conducting semester-starting seminars can aid students in managing stress and enhancing their academic and clinical performance.